Investigation on aerodynamic performance of vertical axis wind turbine with different series airfoil shapes. (October 2018) - Wang, Ying; Shen, Sheng; Li, Gaohui; Huang, Diangui; Zheng, Zhongquan
Abstract: Numerical research for vertical axis wind turbine with different thicknesses or different cambers of airfoils was conducted in this paper. By comparing with the experiment results, the simulation results were validated. Power coefficients under different tip speed ratios were calculated and compared for different types of airfoils: ① symmetrical airfoils with same maximum thickness position, but different maximum thicknesses; ② symmetrical airfoils with same maximum thickness, but different maximum thickness positions; ③ non-symmetrical airfoils with same maximum thickness, same maximum thickness position, same maximum camber position, but different maximum cambers; ④ non-symmetrical airfoils with same maximum thickness, same maximum thickness position, same maximum camber, but different maximum camber positions. It was found that power coefficient of VAWT showed tendency at first increase and then decrease with the increase of tip speed ratio for symmetrical airfoils with same maximum thickness and same maximum thickness position. Moreover, when the maximum thickness position moved from the leading edge to trailing edge, the power coefficient firstly increased and then decreased for symmetrical airfoils with the same maximum thickness but different maximum thickness positions. Besides, with the rise of areas enclosed by curves of surface pressure coefficient when the azimuthal position increases from 0° to 90°, there showed much larger work capability. Highlights: Simulation results were compared with experimental results for validation. Power coefficient with different hydrofoil shapes was numerically investigated. Power coefficient of VAWT varies with maximum thickness and its position. Power coefficient of VAWT also varies with maximum camber and its position.